(untitled) (Conferencea, 2023)
This article presents the development of an innovative experimental model of pulmonary fibrosis in rats and investigates its pathological consequences. Pulmonary fibrosis is a devastating and poorly understood lung disease that leads to tissue scarring and impaired respiratory function. In this study, a robust rat model was established through a combination of precise inducement methods, allowing for the systematic examination of fibrotic progression, biomarkers, and potential therapeutic interventions. The findings shed light on the complex mechanisms underlying pulmonary fibrosis and offer valuable insights for future research and drug development in the quest to combat this debilitating condition.